Genomic Characterization of the Periwinkle Leaf Yellowing (PLY) Phytoplasmas in Taiwan - Cho, Shu-Ting; Lin, Chan-Pin; Kuo, Chih-Horng (Frontiers in Microbiology, 2019)
The periwinkle leaf yellowing (PLY) disease was first reported in Taiwan in 2005. This disease was caused by an uncultivated bacterium in the genus ‘Candidatus phytoplasma’. In subsequent years, this bacterium was linked to other plant diseases and caused losses in agriculture. For genomic investigation of this bacterium and its relatives, we conducted whole genome sequencing of a PLY phytoplasma from an infected periwinkle collected in Taoyuan. The de novo genome assembly produced eight contigs with a total length of 824,596 bp. The annotation contains 775 protein-coding genes, 63 pseudogenes, 32 tRNA genes, and two sets of rRNA operons. To characterize the genomic diversity across populations, a second strain that infects green onions in Yilan was collected for re-sequencing analysis. Comparison between these two strains identified 337 sequence polymorphisms and 10 structural variations. The metabolic pathway analysis indicated that the PLY phytoplasma genome contains two regions with highly conserved gene composition for carbohydrate metabolism. Intriguingly, each region contains several pseudogenes and the remaining functional genes in these two regions complement each other, suggesting a case of duplication followed by differential gene losses. Comparative analysis with other available phytoplasma genomes indicated that this PLY phytoplasma belongs to the 16SrI-B subgroup in the genus, with ‘Candidatus Phytoplasma asteris’ that causes the onion yellowing (OY) disease in Japan as the closest known relative. For characterized effectors that these bacteria use to manipulate their plant hosts, the PLY phytoplasma has homologs for SAP11, SAP54/PHYL1, and TENGU. For genome structure comparison, we found that potential mobile unit (PMU) insertions may be the main factor that drives genome rearrangements in these bacteria. A total of 10 PMU-like regions were found in the PLY phytoplasma genome. Two of these PMUs were found to harbor one SAP11 homolog each, with one more similar to the 16SrI-B type and the other more similar to the 16SrI-A type, suggesting possible horizontal transfer. Taken together, this work provided a first look into population genomics of the PLY phytoplasmas in Taiwan, as well as identified several evolutionary processes that contributed to the genetic diversification of these plant-pathogenic bacteria.